Diallyl trisulfide inhibits the metastasis of anaplastic thyroid carcinoma cells by targeting TGF-β-Smad3-integrin α2β1 signaling pathway. (January 2023) - Wang, Yunping; Xu, Shichen; Cheng, Xian; Wu, Jing; Yu, Huixin; Bao, Jiandong; Zhang, Li; Lu, Rongrong
Abstract: Diallyl trisulfide (DATS), a natural sulfide present in allicin, has been documented as an effective anti-cancer agent against various carcinomas. Anaplastic thyroid carcinoma (ATC) is the most lethal histologic type of thyroid carcinoma. Over 80% of patients are found to have metastasis when they are diagnosed with ATC. Our previous researches indicated that DATS could induce apoptosis and compromise the stem cell phenotype of thyroid carcinoma. However, the effect of DATS on ATC metastasis is still unclear. The present study demonstrated that DATS could inhibit the migration, invasion, cell adhesion and spreading of ATC cells. Mechanistically, the process of epithelial-mesenchymal transition (EMT) was reversed by DATS treatment, evidenced as the decreased Slug expression. Integrins are the major receptors of extracellular matrix (ECM) components which regulate the migration and proliferation of cells. We found that integrin α2β1 was upregulated in ATC tissues. DATS could downregulate both the expression and membrane localization of integrin α2β1 in ATC cells. Our results suggested that DATS was capable of suppressing ATC cells metastasis. Besides, the expression of integrin α2β1 in ATC cells triggered by TGF-β were further inhibited after DATS treatment. These findings suggested that DATS showed bioactivity to serve as a plant intervention ingredient. Graphical Abstract: ga1 Highlights: Diallyl trisulfide inhibited metastasis of anaplastic thyroid carcinoma cells. Integrin α2β1 is overexpressed in anaplastic thyroid carcinoma. Diallyl trisulfide reduced the expression and membrane location of integrin α2β1. TGF-β-Smad3 pathway was associated with expression of integrin α2β1.